2017
DOI: 10.1051/0004-6361/201731245
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium and zirconium abundances in massive Galactic asymptotic giant branch stars revisited

Abstract: Context. Luminous Galactic OH/IR stars have been identified as massive (> 4-5 M ) asymptotic giant branch (AGB) stars experiencing hot bottom burning and Li production. Their Rb abundances and [Rb/Zr] ratios, as derived from classical hydrostatic model atmospheres, are significantly higher than predictions from AGB nucleosynthesis models, posing a problem to our understanding of AGB evolution and nucleosynthesis. Aims. We report new Rb and Zr abundances in the full sample (21) of massive Galactic AGB stars, pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…11 are located where they were expected to be. Nevertheless, several studies (García-Hernández et al 2006Pérez-Mesa et al 2017) point out that some of these stars are intermediate rather than low-mass O-rich AGB stars, i.e. they should be found in Fig.…”
Section: Characterisation Of Carbon Stars With the Gaia-2mass Diagrammentioning
confidence: 99%
“…11 are located where they were expected to be. Nevertheless, several studies (García-Hernández et al 2006Pérez-Mesa et al 2017) point out that some of these stars are intermediate rather than low-mass O-rich AGB stars, i.e. they should be found in Fig.…”
Section: Characterisation Of Carbon Stars With the Gaia-2mass Diagrammentioning
confidence: 99%
“…The s-process element Rb, being a good indicator of the progenitor mass in AGB stars (see e.g. García-Hernández et al 2006;Pérez-Mesa et al 2017), has been also measured in these stars. Contrary to the synthesis of Li, strong Rb production is expected towards the end of the AGB phase, when a significant number of TPs have been experienced (see e.g.…”
Section: Lithiummentioning
confidence: 99%
“…i) AGB stars: both C-rich and O-rich AGB stars may not display the final chemical composition and their chemical abundance analysis (especially towards the end of the AGB, where they are usually dust enshrouded; i.e., optically invisible) is very complicated due to their complex dynamical atmospheres, which can dramatically affect the derived abundances (see e.g. Zamora et al 2014;Pérez-Mesa et al 2017). The CNO elemental and isotopic abundances, as obtained from high-resolution optical and/or near-IR spectroscopy, are only available in some Galactic C-rich AGB stars (e.g.…”
Section: Observational Facts and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 of Karinkuzhi et al (2018b). Observations of massive AGB stars have confirmed that these stars in fact produce Rb (García-Hernández et al 2006, although a quantitative mismatch with the models is still present (van Raai et al 2012;Karakas et al 2012) and currently being investigated (Pérez-Mesa et al 2017).…”
Section: The Case Of Stellar Rotationmentioning
confidence: 99%